2014
DOI: 10.1111/1462-2920.12421
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and antimicrobial resistance genes in marine bacteria from salmon aquaculture and non‐aquaculture sites

Abstract: Antimicrobial resistance (AR) detected by disc diffusion and antimicrobial resistance genes detected by DNA hybridization and polymerase chain reaction with amplicon sequencing were studied in 124 marine bacterial isolates from a Chilean salmon aquaculture site and 76 from a site without aquaculture 8 km distant. Resistance to one or more antimicrobials was present in 81% of the isolates regardless of site. Resistance to tetracycline was most commonly encoded by tetA and tetG; to trimethoprim, by dfrA1, dfrA5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 73 publications
(128 reference statements)
4
82
2
6
Order By: Relevance
“…The prevalence of resistant bacteria carrying ARGs (Nonaka et al, 2007; Shah et al, 2014) and enrichment of ARGs in sediments below fish farms have been observed globally (Tamminen et al, 2011a; Gao et al, 2012; Muziasari et al, 2014, 2016; Xiong et al, 2015). However, the causes of ARG enrichment in the farm sediments have received very little attention.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of resistant bacteria carrying ARGs (Nonaka et al, 2007; Shah et al, 2014) and enrichment of ARGs in sediments below fish farms have been observed globally (Tamminen et al, 2011a; Gao et al, 2012; Muziasari et al, 2014, 2016; Xiong et al, 2015). However, the causes of ARG enrichment in the farm sediments have received very little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, antibiotics are poorly absorbed and metabolized by the tested organisms (Sarmah et al, 2006); hence, most of these chemicals have ultimately entered the environment via urine and feces, domestic swage, livestock and agriculture wastes, and/or direct splashing to the aquaculture water (Heuer et al, 2008;Yao et al, 2015;Shah et al, 2014). Due to their continuous input into the environment through numerous pollution sources and their degradation-resistant characteristics, antibiotics are regarded as a class of ubiquitous and "pseudo-persistent" contaminants in aquatic environments (Nödler et al, 2012;Yao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although antibiotic resistance is ancient and naturally occurring phenomenon widespread in the environment [3], it is accelerated by antibiotic use in medicine and veterinary. The spread of ARGs in the environment is promoted by anthropogenic activities, such as animal farm [4], waste/wastewater treatment [5], and aquaculture [6]. To our knowledge, ARGs have been investigated in several environmental compartments, such as farm lands [7], rivers [8], and fish ponds [9].…”
Section: Introductionmentioning
confidence: 99%